2007
DOI: 10.1300/j037v16n03_05
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Trust in Electronic Service Consumption: A Cross-Cultural Comparison Between Finland and Portugal

Abstract: Lack of trust has been identified as a major barrier to consumer acceptance of e-commerce. This empirical study examines consumer trust in electronic service consumption in a cross-cultural setting, comparing perceived trust between Finnish and Portuguese Internet banking users. Consumer trust is a significant factor both in consumer attitudes and behavioral intention to using Internet banking. Consumer trust in Internet banking is reflected as the trust in the information and trust in the medium, that is, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 39 publications
0
26
0
1
Order By: Relevance
“…Morgan and Hunt (1994) demonstrated that path relationships between trust, commitment, and loyalty are different between females and males. In the context of online financial services, Kivijärvi, Laukkanen, and Cruz (2007) argued that it is meaningful to test the role of gender in trust-based research models, and more recently, Ladhari and Leclerc (2013) demonstrated that genders differ in their perceptions of website service quality, e-satisfaction, e-trust, and e-loyalty.…”
Section: Gender Differencesmentioning
confidence: 99%
“…Morgan and Hunt (1994) demonstrated that path relationships between trust, commitment, and loyalty are different between females and males. In the context of online financial services, Kivijärvi, Laukkanen, and Cruz (2007) argued that it is meaningful to test the role of gender in trust-based research models, and more recently, Ladhari and Leclerc (2013) demonstrated that genders differ in their perceptions of website service quality, e-satisfaction, e-trust, and e-loyalty.…”
Section: Gender Differencesmentioning
confidence: 99%
“…An experimental study by Mutz (2005) also indicated that increasing levels of social trust encouraged greater intention to purchase online. While trust is central to marketing and marketing relationships, there is still a dearth of published work on trust in the field of marketing (Arnott, 2007), especially the cross‐cultural research on the topic (Kivijärvi et al ., 2007).…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…A recent study by Kivijärvi et al . (2007) examined the role of culture (individualism and uncertainty avoidance) in consumer trust in the context of online banking.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…First, data support in general the conceptual framework presented. However, some mentions need to be made: (i) trust and convenience, from all the elements referenced in the literature as relevant from the client' perspective, continue to be a very important elements [2,3,[28][29][30]; (ii) the results did not support the paradigm that the characteristics of individuals affect their behavior as consumers, which contradicts the conclusions of Sadiq and Shanmugham [27]; (iii) individual technological characteristics affect consumer adoption of internet banking service; (iv) consumer perceptions over the Internet Banking service affect their use, as reveal by the existence of three types of customers that show different practices and perceptions of IB; and (v) intention to use internet banking is dependent upon attitudes towards the use of internet banking and subjective norms about the use of internet banking. These last results are consistent with the literature, in particular the models of adoption of new technologies proposed by Eriksson and Such (2008) and by Alsajjan and Dennis [23].…”
Section: Contributions and Implicationsmentioning
confidence: 99%